Experimental Performance Investigation of an Original Rotating Solar Still Design under Realistic Meteorological Conditions - Faris Alqurashi; Rached Nciri; Abdulrahman Alghamdi; Chaouki Ali; Faouzi Nasri (Energies, 2022)
This research article proposes a novel design of solar still; furthermore, it investigates, experimentally, its thermal and productivity performances, as well as its efficiency, under the realistic meteorological conditions of the city of Gafsa, Tunisia (34.4311° N, 8.7757° E), in terms of ambient temperature and solar irradiance. The novel proposed design presents a cylindrical solar still with a rotating transparent plastic (Plexiglass) cover, wiped continuously on the inner surface. A specific technological configuration of the evaporation and condensation compartments is elaborated. A real prototype is manufactured in order to carry out the performance experimental investigation. A performance comparison is carried out between the cylindrical transparent plastic cover rotating and it being fixed, for two experimentation days presenting slightly different meteorological conditions. The experimental water and plastic cover temperatures, the hourly and the cumulative water production, as well as the hourly efficiency are deeply quantified and interpreted.